Prevalence of Staphylococcus aureus colonization in renal transplant patients - Luiz Carlos Ribeiro Lamblet; Dulce Aparecida Barbosa (SciELO, 2014)
Objective to evaluate the prevalence of Staphylococcus aureus nasal colonization in renal transplant patients and to identify the related risk factors. Method Swabs were used to collect nasal samples from 160 patients who had undergone a transplant within the previous year at the Kidney and Hypertension Hospital. The 'National Committee for Clinical Laboratory Standards' norms were followed for the collection, isolation, identification and sensitivity measurements. Results There was a 9.4% (15) prevalence of Staphylococcus aureus nasal colonization, of which one (6.7%) was resistant to oxacillin. It was possible to identify as an associated risk factor a wait of more than one year for accessing dialysis prior to the transplant (p=0.029). Conclusion Given the high morbidity and mortality rates that this microorganism causes in the target population, other studies should be carried out, and pre- and post-transplant screening should occur in order to develop strategies that improve the prevention and control of the spread of Staphylococcus aureus.